2021
DOI: 10.18311/jnr/2021/26255
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Phytotherapy in BALB/c Athymic Nude Mice: Hair Growth Promotion using <i>Ficus religiosa</i> L. and <i>Morus alba</i> L.

Abstract: <em>Ficus religiosa</em> L. (FR) and <em>Morus alba</em> L. (ML) belonging to the family Moraceae have been tested as novel herbal agents for hair growth promotion and Hair Follicles (HFs) regeneration in BALB/c athymic nude mouse model. Current study tested different mixtures of 5% aqueous fractions: Test 1 (ML2+ML3+ML4+FR4), Test 2 (FR1+FR2+FR4), or Test 3 (ML2+ML3+ML4+FR1+FR2+FR4) from leaves of both plants including standard of care 2% minoxidil. Control mice were untreated. Animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Joshi et al reported that the mixture of aqueous fractions of Ficus religiosa L. and M. alba L. leaf extract (topical application for 28 days) promoted hair growth and hair follicles regeneration by inducing the anagen phase in BALB/c athymic nude mice [ 100 ].…”
Section: Role Of Phytochemicals In Hair Growthmentioning
confidence: 99%
“…Joshi et al reported that the mixture of aqueous fractions of Ficus religiosa L. and M. alba L. leaf extract (topical application for 28 days) promoted hair growth and hair follicles regeneration by inducing the anagen phase in BALB/c athymic nude mice [ 100 ].…”
Section: Role Of Phytochemicals In Hair Growthmentioning
confidence: 99%